Development of Jogja Tourism App using GPS-Based Tracking Augmented Reality - Hardika Dwi Hermawan; Azis Amirulbahar; Dita Puji Rahayu; Miftah Rizki Hanafi; Yuni Setya Ningsih; Sidik Nurcahyo (Universitas Negeri Padang, 2022)
The number of tourists every year continues to increase, but the pandemic resulted in tourists experiencing a decrease, and activity also prioritized social distancing. With the reduction of tourists and human interaction, media are needed to help tourists still visit Jogja by minimizing interaction. The method used to build applications in Research and Development. The first stage is the need analysis and literature study. The second stage is a design that uses use-case diagram. The third stage is implementing or developing applications and quality assurance testing. The fourth stage is the stage of testing software for users and knowing the feasibility of the application. The results showed that the results of the application work were excellent, with a percentage of 85.11%, which means the application is suitable for the Jogja Tourism App.